Cauda Equina Syndrome - El-Varel Baby Berlianzsa; Rosha Aulia Fadhilah Hafidz (Institute of Computer Science (IOCS), 2022)
Cauda equina syndrome (CES) is a rare condition in which the lumbosacral nerve roots that extend below the spinal cord itself are compressed within the lumbosacral spinal canal. Cauda equina syndrome (CES) is a devastating condition for quality of life which may lead to permanent disability with associated neurological pain affecting the patient, their family and relationships. We hereby present a case regarding 31-year-old man with features of cauda equina syndrome. A In this patient MRI was done and revealed degeneration of the lumbar discs, specifically on the L3-4 and L5-S1 segments, which could possibly be preceded by disc herniations (10-12). The spinal cord micturition center is located at S2–S4 levels (anatomi- cally near the L1 vertebrae). Injuries leading to bladder dysfunction may result in detrusor hyperreflexia and detrusor sphincter dyssynergia in suprasacral injuries and detrusor areflexia in sacral injuries. Based on clinical and laboratory examination results, The patient was diagnosed with cauda equina syndrome. Symptomatic measures were then given to the patient, which include codeine 3x10 mg, pregabalin 3x50mg, potassium chloride 2x25 mEq, ketorolac 3x10 mg, and ceftriaxone 1x2 g.